2015
DOI: 10.5194/piahs-370-177-2015
|View full text |Cite
|
Sign up to set email alerts
|

Extensive spatio-temporal assessment of flood events by application of pair-copulas

Abstract: Abstract. Although the consequences of floods are strongly related to their peak discharges, a statistical classification of flood events that only depends on these peaks may not be sufficient for flood risk assessments. In many cases, the flood risk depends on a number of event characteristics. In case of an extreme flood, the whole river basin may be affected instead of a single watershed, and there will be superposition of peak discharges from adjoining catchments. These peaks differ in size and timing acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…The R-vine copula was thanks to its flexible structure able to reproduce the general dependence structure. This is in line with findings by Schulte and Schumann (2015), who worked with pair-copula constructions and found that the use of flexible Archimedean copulas allowed representation of spatial dependence in flood event data. This is essentially due to the fact that Archimedean copulas can model asymmetric lower and upper tail dependence, but they are only available for lower dimensions.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The R-vine copula was thanks to its flexible structure able to reproduce the general dependence structure. This is in line with findings by Schulte and Schumann (2015), who worked with pair-copula constructions and found that the use of flexible Archimedean copulas allowed representation of spatial dependence in flood event data. This is essentially due to the fact that Archimedean copulas can model asymmetric lower and upper tail dependence, but they are only available for lower dimensions.…”
Section: Discussionsupporting
confidence: 91%
“…Spatial dependence was found to be important because no single event caused the maximum flood extent at all locations and assuming perfect correlation between tributaries overestimated flood hazard (Neal et al, 2013). A multivariate approach is therefore needed which represents the spatial dependence between floods from different watersheds (Schulte and Schumann, 2015) which might be radially asymmetric and show non-null tail dependence since more extreme events might be more strongly related than less extreme events. A multivariate approach should allow for the generation of stochastic event sets at multiple stations and for the consideration of the network structure of the catchment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The R-vine copula was thanks to its flexible structure able to reproduce the general dependence structure. This is in line with findings by Schulte and Schumann (2015) who worked with pair copula constructions 5 and found that the use of flexible Archimedean copulas are able to represent spatial dependence in flood event data. This is essentially due to the fact that Archimedean copulas can model asymmetric lower and upper tail dependence but they are only available for lower dimensions.…”
Section: Discussionsupporting
confidence: 91%